Analisis Pengaruh Anggaran Biaya Produksi Dan Kas Terhadap Anggaran Perencanaan Dan Pengendalian Perusahaan: Literature Review - Oky Resita Rahmania (Jurnal Riset Ekonomi dan Akuntansi, 2024)
The purpose of this study was to analyze the influence of the budget of production costs and cash costs on the planning and control budgets of trading companies. The method used is the qualitative method with the study of the library. The results in this article are summarized as follows: (1) The budget of production costs has an effect on the Company's Control Budget (2) The cash budget has an effect on the Company's Control Budget.